Tavsanli Creek (Sivas-Hafik) Flood Risk Analysis - Sengun, M. Taner; Karadeniz, Enes; Saman, Busra (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Tavsanli Creek, which is the subject of research, is located in Kizilirmak basin; It is located within the boundary of Hafik district of Sivas province. The purpose of this research; Tavsanli Creek Basin with a high risk of flood and 370km(2) area; the risk of settlements and large agricultural lands is to determine the losses and damages of the settlements established in the floodplain during a possible flood and to minimize the damages that may occur. In this study, two different methods which are remote sensing and geographic information based Multi Criteria Decision Making Methods have been used to determine possible risky regions and settlements that will be damaged during flooding of Tavsanli Creek Basin which is under the risk of flood. Since the accuracy of the data presented in the flood studies was significant, two methods were compared and their suitability for the basin was determined. One of the methods used is Analytical Hierarchy Method which is one of Multi Criteria Decision Making methods. In line with this method, DEM has been produced from 1/25000 digital topographic data and GPS points. Besides, land use and ground cover of the basin were determined by means of field work and data to be used in the study were formed. The other method used in the study is weighted overlay, another of the multi critical decision-making methods. The same data produced was also used in this method and the percentages of the data were entered equally in both methods. Through these methods, the mapping of the places under the risk of possible floods has been made.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Tavsanli Stream; Multi Criteria Decision Making Method; GIS